An Improved Response of Multi Level Inverter Based PR Controlled SMPS - Sasikala, K.; Krishnakumar, R. (Frontiers in Energy Research, 2020)
This paper mainly focuses on identifying an optimum controller for Multi Level Inverter Based Switched Mode Power Supply (MLIBSMPS) for constant voltage applications. Generally, there is a greater demand of constant voltage for the sensitive loads. A closed loop control is introduced in the circuit in order to obtain constant voltage quickly if there are any disturbances occur at the input side. In this paper, closed loop Proportional Integral (PI) as well as Proportional Resonant (PR) controlled MLI based SMPS systems are simulated and the comparison of their performance is done. It is seen that an acceptable performance is achieved using PR controlled MLI based SMPS than PI Controlled MLI based SMPS. It also proves that PR Controlled SMPS with 7 level inverters has reduced steady state error and improved time domain response as compared to PI Controlled SMPS.